Dans les marges de l’orientalisme britannique : le cas d’Isabella Bird et de Journeys to Persia and Kurdestan (1891) - Laurence Chamlou (Cahiers Victoriens et Edouardiens)
Isabella Bird (1831–1904), explorer, geographer, naturalist, writer and photographer, published Journeys in Persia and Kurdistan in 1891. The experience of travelling was first forced upon her by her state of health. A solitary traveller, she had already published five travelogues. This sixth story is a reflection on the affirmation of identity. Her complex position—juggling with, on the one hand, the Orientalist ideology of her time and, on the other, her commitment to the Kurds, transgressing gender boundaries and adopting modes of representation that were sometimes exotic, sometimes imperialist—also enabled her to assert a voice. This Victorian traveller reveals a triple marginality: that of a literary genre, that of a woman and that of a country (Persia). She became a writer thanks to a genre on the fringes of literature (correspondence and travel writing), to which she added the status of photographer and gained renown during her lifetime. By turning her attention to Persia, she placed herself on the margins of the British Empire, at the heart of the Great Strategic Game between Russia and the United Kingdom. Journeys in Persia and Kurdistan reflects the ambiguities of a woman’s gaze, which mixed politics with adventure, and whose discourse was at once concerned with imperialist power and the search for a status under construction.